Hardware Logic Locking Obfuscation for Cyber Hygiene Based on Hamming Distance Obfuscator - Akhigbe-mudu Thursday Ehis (Research Parks Publishing LLC, 2022)
The circuit netlist, logic locking mode, is an obfuscation method used to protect outsourced chip designs. Logic locking has been demonstrated to be broken via Boolean Satisfiability-based attacks, which has spurred researchers to create more robust defenses. The development of SAT attack marked a turning point in research on logic locking. Software systems frequently update their huge executable code, so obfuscating the program for each small update results in a significant loss of efficiency. In order to provide security guarantees against synthesis-driven assaults, this study provides a transformation strategy. Its Random Technique introduces a novel fault injection attack to undermine any locking mechanism that depends on a saved private key. This made it possible to compare the obfuscated circuit to its source, to determine whether a sufficient structural change has been made to support its functionality. The RT created an attack strategy to discover the value of the private key, K*. It examines the SFLL's security and offered a solution to determine the hamming distance,